How Are The Children Of Immigrants Assimilating? The Effects Of Individual, Neighborhood, Coethnic Community, And National Origin Group Characteristics On Education In San Diego - Rennie Lee (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
How immigrants’ children will integrate to US society is of ongoing debate. This study examines which assimilation pathway immigrants’ children are following. This study examines how four factors—individual, neighborhood, coethnic community, and national origin group—affect the children of immigrants’ educational attainment. I analyze a unique data set that matches individual survey data from the Children of Immigrants’ Longitudinal Survey (CILS) dataset with coethnic community, neighborhood, and group level data. The results indicate that coethnic community, group, and individual factors simultaneously influence the children of immigrants’ education, showing evidence for the selective assimilation pathway.